2019
DOI: 10.1017/s0950268819001365
|View full text |Cite
|
Sign up to set email alerts
|

The distinct epidemic characteristics of HCV co-infection among HIV-1-infected population caused by drug injection and sexual transmission in Yunnan, China

Abstract: Hepatitis C virus (HCV) infection was frequent in human immunodeficiency virus (HIV) patients in Yunnan province. We studied the epidemic characteristics of HCV in HIV/HCV co-infected patients. Serum from 894 HIV-1 patients was collected, together with basic information and biochemical features. All samples were infected with HIV through injecting drug users (IDUs) and sexual transmission (ST). The NS5B gene was amplified and sequenced to affirm HCV genotype. In total, 202 HIV patients were co-infected with HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This study revealed that the main circulating HCV subgenotypes among HIV/HCV-coinfected patients in Guangdong were 6a (58.28%, 176/302), followed by 1b (18.54%, 56/302), 3a (10.93%, 33/302), 3b (6.95%, 21/302), 1a (3.64%, 11/302), 2a (0.99%, 3/302), and 6n (0.66%, 2/302). The predominant HCV subgenotypes among HIV/HCV-coinfected individuals in Guangdong were similar to those in Guangxi (6a (46%), 3a (20%), 3b (16%)) [27] but distinct from those in Yunnan (3b (37.62%), 3a (23.76%), 1b (16.34%)) [28]. HCV genotypes vary in the Asia-Pacific region [29], HCV infections and HIV infections have the common transmission route of sharing contaminated injecting equipment, sexual transmission and blood related transmission [29].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This study revealed that the main circulating HCV subgenotypes among HIV/HCV-coinfected patients in Guangdong were 6a (58.28%, 176/302), followed by 1b (18.54%, 56/302), 3a (10.93%, 33/302), 3b (6.95%, 21/302), 1a (3.64%, 11/302), 2a (0.99%, 3/302), and 6n (0.66%, 2/302). The predominant HCV subgenotypes among HIV/HCV-coinfected individuals in Guangdong were similar to those in Guangxi (6a (46%), 3a (20%), 3b (16%)) [27] but distinct from those in Yunnan (3b (37.62%), 3a (23.76%), 1b (16.34%)) [28]. HCV genotypes vary in the Asia-Pacific region [29], HCV infections and HIV infections have the common transmission route of sharing contaminated injecting equipment, sexual transmission and blood related transmission [29].…”
Section: Discussionmentioning
confidence: 71%
“…Guangxi Province, which borders Vietnam, could have been the first region to contract 6a for circulation. Genotype 6a was introduced into Guangxi from Vietnam and then further spread to Guangdong through drug trafficking routes and IDU networks [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…It could be argued that drug-injecting MSM were the bridge between the two viral communities (14). However, the distinct genotype distributions among risk groups could only be explained by founder effect (25,26). It is likely that only a fraction of the HCV co-infections could be attributable to their needle sharing behavior (27).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the prevalence of HCV infection is different in different populations. For example, the prevalence of HCV infection in premarital screening population was 0.3%, 14 while that of intravenous drug user population was ranging from 22% to 95% 15 . Therefore, this study set the different prevalence of HCV infection in the population (0.5%, 1% and 10%, respectively), and combined with clinical sensitivity and specificity to calculate PPV and NPV.…”
Section: Discussionmentioning
confidence: 99%